Harry at the dog show - Driscoll, Laura; Zion, Gene; Graham, Margaret Bloy; Joshaghani, Saba (2023)
While at a dog show in the park, Harry, a little white dog with black spots, accidentally finds himself in the middle of an obstacle course and tries to find a way out!
"Based on the character created by Gene Zion and Margaret Bloy Graham"
Guided Reading
Keywords: Harry (Fictitious character : Zion) -- Juvenile fiction; Dogs -- Juvenile fiction; Dog shows -- Juvenile fiction; Picture books; Dogs -- Fiction; Dog shows -- Fiction; Picture books; picture books; JUVENILE FICTION / Animals / Dogs; Dog shows; Dogs; Harry (Fictitious character : Zion); Harry (Fictitious character : Zion) -- Juvenile fiction; Dogs -- Juvenile fiction; Dog shows -- Juvenile fiction; Harry (Fictitious character : Zion) -- Fiction; Dogs -- Fiction; Dog shows -- Fiction; Readers (Elementary); Children's stories; readers; picture books; Fiction; Juvenile works; Picture books; Animal fiction; Readers (Publications); Picture books